Modelling the impacts of reforestation on the projected hydroclimatology of Niger River Basin, West Africa. Issue 1 (8th November 2012) - Oguntunde, Philip G.; Abiodun, Babatunde J.; Lischeid, Gunnar; Merz, Christoph
ABSTRACT This study simulates the impacts of reforestation on hydroclimatology of Niger River Basin (NRB) under enhanced greenhouse gases (GHGs). A regional climate model (RegCM3) was used to dynamically downscale hydroclimatological variables of NRB for present‐day (PRS), and for future climate scenarios (with and without reforestation). The data were further analysed to detect changes in water balance components and the moisture recycling ratios. Under A1B scenario, warmer climate was projected over the entire basin in all seasons, a drier climate during the rainy season, and a wetter climate during the dry season. Reforestation along NRB (GBR) reduces the GHG warming over the basin both seasons, but increases it north‐east of the basin in July–September (JAS). Both reforestation scenarios could enhance rainfall over the reforested area. With reforestation over Sahel (GSR), seasonal evapotranspiration increases between 3·6% and 14·4%; but with GBR, evapotranspiration reduces between −12·4% and −4·3%. The GSR option offsets the projected annual GHG effects on moisture recycling over the basin. Evaporation coefficient decreased by about 5% under elevated CO2 while runoff coefficient increased. Reforestation reduces the projected warming and drying over the reforested zones because of its influence on the monsoon flow (reduction in speed). Hence, with reforestation in summer, the onset of monsoon delays in bringing in the cool moist air over the area located downwind of the reforested zone; this increases the temperature and reduces rainfall amount over the area. Copyright © 2012 John Wiley & Sons, Ltd.